Evaluasi User Experience Sistem Informasi TboticsEducation menggunakan User Experience Questionnaire (UEQ) pada Tbotics Jakarta - Firman Adji Sanjaya; Rangga Pratama Dewantoro; Mohammad Ali Hibrizi; Yuni Fitriani; Safitri Linawati (Jurnal Teknik Informatika dan Teknologi Informasi, 2026)
Innovations in the field of information technology emphasize how crucial it is to evaluate user experience in order to provide top-notch digital services. The purpose of this study is to apply the User Experience Questionnaire (UEQ) approach to assess the Linkin.bio/TboticsEducation website's user experience. One hundred users who had engaged with the site were given questionnaires as part of a quantitative approach. Attractiveness, Perspicuity, Efficiency, Dependability, Stimulation, and Novelty were the six UEQ qualities covered by the 26 questions that made up the research instrument. The findings of the instrument evaluation showed that every questionnaire item had very high reliability (a Cronbach's Alpha value of 0.940) and was valid (calculated r-values exceeded the critical r-table value of 0.195). Attractiveness (1.55), Perspicuity (1.56), Efficiency (1.64), Dependability (1.51), Stimulation (1.33), and Novelty (1.12) were all shown to have positive mean ratings. Based on UEQ benchmarks, the Efficiency and Dependability dimensions fell into the "Good" category, while Attractiveness, Perspicuity, Stimulation, and Novelty fell into the "Above Average" category. These results indicate that the Linkin.bio/TboticsEducation website provides a satisfying user experience and effectively meets user needs in supporting the learning of robotics systems. However, the Stimulation and Novelty aspects require improvement through the development of more innovative and engaging features to enhance the overall quality of the user experience.